Pengaruh Media Sosial terhadap Perilaku Konsumtif Mahasiswa - Dini Alfitriyani (Terekam Jejak Publisher, 2023)
Student consumptive behavior can be described through several aspects of individual interests, in the current era the use of social media will influence individuals in choosing shopping choices. Social media does not only function to seek entertainment, for education, work, or study, but this research underlines the use of social media in shopping aspects. This study uses 2 instruments to see the effect between variables and uses a cross sectional survey method. There were 24 respondents who were collected with an age range of 16-24 years to describe student behavior in using social media towards consumptive behavior. This research describes the use of social media and consumer behavior by students. There are 8 questions from social media variables and there are 8 questions and statements totaling 8 from consumptive behavior variables. Especially on the question